Smoking cessation, but not reduction, reduces cardiovascular disease incidence. (25th August 2021) - Jeong, Su-Min; Jeon, Keun Hye; Shin, Dong Wook; Han, Kyungdo; Kim, Dahye; Park, Sang Hyun; Cho, Mi Hee; Lee, Cheol Min; Nam, Ki-Woong; Lee, Seung Pyo
Abstract: Aims: The aim of this study was to assess the association of smoking cessation and reduction with risk of cardiovascular disease (CVD). Methods and results: A total of 897 975 current smokers aged ≥40 years who had undergone two consecutive national health examinations (in 2009 and 2011) were included. Participants were classified as quitters (20.6%), reducers I (≥50% reduction, 7.3%), reducers II (20–50% reduction, 11.6%), sustainers (45.7%), and increasers (≥20% increase, 14.5%). During 5 575 556 person-years (PY) of follow-up, 17 748 stroke (3.2/1000 PY) and 11 271 myocardial infarction (MI) (2.0/1000 PY) events were identified. Quitters had significantly decreased risk of stroke [adjusted hazard ratio (aHR) 0.77 95% confidence interval (CI) 0.74–0.81; absolute risk reduction (ARR) −0.37, 95% CI −0.43 to −0.31] and MI (aHR 0.74, 95% CI 0.70–0.78; ARR −0.27, 95% CI −0.31 to −0.22) compared to sustainers after adjustment for demographic factors, comorbidities, and smoking status. The risk of stroke and MI incidence in reducers I (aHR 1.02, 95% CI 0.97–1.08 and aHR 0.99, 95% CI 0.92–1.06, respectively) and reducers II (aHR 1.00, 95% CI 0.95–1.05 and aHR 0.97, 95% CI 0.92–1.04, respectively) was not significantly different from the risk in sustainers. Further analysis with a subgroup who underwent a third examination (in 2013) showed that those who quit at the second examination but had starting smoking again by the third examination had 42–69% increased risk of CVD compared to sustained quitters. Conclusions: Smoking cessation, but not reduction, was associated with reduced CVD risk. Our study emphasizes the importance of sustained quitting in terms of CVD risk reduction. Graphical Abstract: